LAJU PENINGKATAN KONSENTRASI TIMBAL (Pb) DALAM DARAH HEWAN UJI MENCIT (Mus musculus) DI BENGKEL OTOMOTIF - Mohammad Razif; Sukatma Sukatma (The East Java Biological Society, 2004)
This research was conducted in automotive workshop of VEDC Malang and the samples were taken at the automotive machine and automotive electric workshops. The parameters which examined were the Pb concentration in the mouse blood (Mus musculus) in 2 and 3 months years old. The measurement was run for 5 times every 10 days, and the result was mean value of the increasing rate of Pb concentration in the mouse blood. The aim of this research was to determine the increasing rate of Pb concentration in the mouse blood which has the relation with different working area, different age, and also duration of exposure. Based on the data of laboratory test, research continued by T-test analysis, Simple regression test, and correlation, and also General Linear Model. By doing statistic analysis with the different working area, duration of explanation, and different age.Result of this research showed that there were the differences of rapid increasing of Pb concentration in both workshop. Generally the age which influence so much for that (in the mouse body) and have the relation with the body stamina. If the mouse body absorb amount of Pb constantly, so the Pb concentration in it will increase more and more and it cause the decreasing of the body height.